Antibiotic resistance and heavy metal tolerance in cultured bacteria from hot springs as indicators of environmental intrinsic resistance and tolerance levels. (June 2019) - Jardine, Jocelyn; Mavumengwana, Vuyo; Ubomba-Jaswa, Eunice
Abstract: Antibiotic resistance (AR) in the environment is a growing and global concern for public health, and intrinsic AR from pristine sites untouched by pharmaceutical antibiotics is not commonly studied. Forty aerobic bacteria were isolated from water and sediment samples of hot springs in South Africa. Resistance against ten antibiotics (carbenicillin, gentamicin, kanamycin, streptomycin, tetracycline, chloramphenicol, ceftriaxone, co-trimoxazole, nalidixic acid and norfloxacin) was tested using a standard disk diffusion assay. Resistance to one or two antibiotics were equally found in 37.5%, while the remaining 22% showed complete sensitivity. Intermediate resistance was found for ceftriaxone (52.5%), nalidixic acid (37.5%) and carbenicillin (22.5%), while low levels of resistance were observed for streptomycin (5%) and kanamycin (2.5%), and total sensitivity towards the other antibiotics. Twenty-nine isolates were also tested against eight different heavy-metal salts (Al, Cr, Cu, Fe, Hg, Mn, Ni and Pb) at 10 and 40 mM. All isolates were tolerant and able to grow on ≥2 heavy-metal salts at both concentrations. No association was observed between AR and heavy metal tolerance (HMT). Based on the relatively low AR levels, hot spring sites are pristine environments reflecting baseline levels for comparison to other potentially contaminated groundwater sites. Graphical abstract: Image 1 Highlights: Hot spring bacteria were tested against 10 antibiotics and 8 heavy metal salts. Resistance found against ceftriaxone>nalidixic acid>carbenicillin. All isolates grew on ≥2 heavy-metal salts at 10 and 40 mM concentrations. Low antibiotic resistance in pristine sites may reflect baseline antibiotic resistance levels. Abstract : Antibiotic resistance (AR) in the environment is a growing and global concern for public health. Based on the relatively low AR levels, hot spring sites are pristine environments reflecting baseline levels for comparison to other potentially contaminated sites.